Characterization of combined blast- and fragments-induced synergetic damage in polyurea coated liquid-filled container - Chen Tao; Chong Ji; Xin Wang; Juan Gu; Yuting Wang; Changxiao Zhao (Defence Technology)
Liquid-filled containers (LFC) are widely used to store and transport petroleum, chemical reagents, and other resources. As an important target of military strikes and terrorist bombings, LFC are vulnerable to blast waves and fragments. To explore the protective effect of polyurea elastomer on LFC, the damage characteristics of polyurea coated liquid-filled container (PLFC) under the combined loading of blast shock wave and fragments were studied experimentally. The microstructure of the polyurea layer was observed by scanning electron microscopy, and the fracture and self-healing phenomena were analyzed. The simulation approach was used to explain the combined blast- and fragments-induced on the PLFC in detail. Finally, the effects of shock wave and fragment alone and in combination on the damage of PLFC were comprehensively compared. Results showed that the polyurea reduces the perforation rate of the fragment to the LFC, and the self-healing phenomenon could also reduce the liquid loss rate inside the container. The polyurea reduces the degree of depression in the center of the LFC, resulting in a decrease in the distance between adjacent fragments penetrating the LFC, and an increase in the probability of transfixion and fracture between holes. Under the close-in blast, the detonation shock wave reached the LFC before the fragment. Polyurea does not all have an enhanced effect on the protection of LFC. The presence of internal water enhances the anti-blast performance of the container, and the hydrodynamic ram (HRAM) formed by the fragment impacting the water aggravated the plastic deformation of the container. The combined action has an enhancement effect on the deformation of the LFC. The depth of the container depression was 27% higher than that of the blast shock wave alone; thus, it cannot be simply summarized as linear superposition.